Perbandingan Rituksimab dan Biosimilarnya dalam Regimen Kemoterapi pada Pasien Limfoma Non-Hodgkin di RS Persahabatan - Dendhi Bagus Andriyanto; Nadia Farhanah Syafhan; Fitri Nurhayati (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Non-Hodgkin lymphoma (NHL), particularly diffuse large B-cell lymphoma (DLBCL), represents a significant global and Indonesian health burden. The R-CHOP regimen serves as the standard first-line therapy, with rituximab proven to enhance its efficacy. Following patent expiry, biosimilar rituximab became available. However, real-world effectiveness and safety comparisons, especially within the Indonesian population, remain limited. This retrospective comparative study, conducted at Rumah Sakit Persahabatan, involved NHL patients who received R-CHOP between 2019 and 2024. Medical record data were collected for patients treated with reference rituximab (n=60) and biosimilar rituximab (n=56). Patient characteristics, treatment response based on RECIL 2017 criteria, and adverse events (AEs) based on CTCAE were compared using Chi-Square or Mann-Whitney U tests, with statistical significance set at p<0.05. Baseline patient characteristics were found to be statistically comparable between both groups. Efficacy analysis revealed Complete Response (CR) was numerically higher in reference group (75% vs 58.9% CR), although the difference was not statistically significant (p=0.194). The safety profile generally showed no significant differences for most AEs. However, the incidence of Grade ≥ 3 Herpes was significantly higher in the Biosimilar group (8.3%) compared to the Reference group (0%) (p=0.024). In conclusion, biosimilar rituximab demonstrates comparable efficacy to its reference product in treatment response for NHL patients receiving R-CHOP. Its safety profile is largely comparable, although a notable increase in Herpes incidence was observed in the biosimilar group. These findings support the use of biosimilar rituximab as an effective alternative while underscoring the importance of monitoring specific AEs, particularly Herpes reactivation.